HCV-related chronic kidney disease in the era of new direct-acting antivirals regimens - Jakub Janczura; Kamil Jończyk; Aleksandra Kalisz; Weronika Stepień; Łucja Ilkiewicz; Wiktoria Bisaga; Klaudia Nowak; Paweł Wróbel (Egyptian Liver Journal)
Abstract Chronic hepatitis C virus (HCV) infection has a significant impact on renal health, particularly in the development and progression of chronic kidney disease (CKD). The virus contributes to renal impairment through direct cytopathic effects, immune-mediated injury, and systemic inflammation. Historically, interferon (INF)-based therapies offered limited efficacy and were poorly tolerated, especially among patients with CKD. The emergence of direct-acting antivirals (DAAs) has dramatically changed the treatment landscape, achieving sustained virological response rates exceeding 95%, even in individuals with advanced CKD or those on dialysis. DAAs have proven to be both highly effective and better tolerated, yet challenges remain. These include the need to manage potential drug-drug interactions, address the risk of reinfection, and improve access to therapy globally, particularly in low-resource settings. Initiating treatment requires thorough assessment of renal function, liver status, and coexisting conditions. Further research is needed to evaluate long-term renal outcomes, mortality benefits, and optimal treatment strategies for diverse CKD populations. DAAs represent a major advancement in the management of HCV-related CKD, with the potential to significantly improve patient outcomes and reduce the burden of disease.